Nursing care to the patient in orthopedics: a review by theme analysis (Research, Society and Development, 2023)
Objective: to survey current scientific knowledge regarding nursing care for orthopedic patients. Methodology: the study is an integrative literature review using the thematic analysis technique that was cut from the last five years (2018-2022). Results: the final sample consisted of six articles, the most mentioned themes were nursing care in relation to the integrity of the impaired skin, nursing care in the risk of infection, nursing care in orthopedic pain and the nurse as a member of the multidisciplinary team in orthopedics. Conclusion: through the review, a greater emphasis on nursing diagnoses was noticed, as well as the active participation of the nurse as a member of the team. It is suggested the importance of further studies on the subject, mainly research with the application of nursing diagnoses, validating or not the concepts that are addressed in the literature, bringing behaviors that can be applied to the different environments in which professional nursing care occurs, mainly related to the field of orthopedics and traumatology.